Spearheading ahead to the future a strategic plan for XYZ Corporation - Balinas, Paul Dennis C.; Concepcion, Sylvia B.; Soledad Miguel D. (Davao City School of Management, University of the Philippines Mindanao, 2006)
This paper presents the Five Year Strategic Plan of XYZ Corporation from 2006 to 2010. This is the output of an in-depth analysis of the subject corporation, its performance and its outlook, using a framework adapted from Pearce and Robinson (2000). The study started by looking into the corporate history of XYZ Corporation, then proceeded to formulating the company?s hierarchy of objectives: Vision, Mission and Goals. These objectives were formulated based on the output of the Strategic Planning Workshop participated in by the key management personnel of XYZ Corporation. The study encompasses the analyses of the company?s internal strengths and weaknesses, with particular focus on identifying the company?s core competencies. These competencies were then juxtaposed with the identified external opportunities and threats that XYZ Corporation is likely to face in the next five years to formulate the various strategic options the company might take. Subjecting this arsenal of strategic options to the Quantitative Strategic Planning Matrix as decision-making tool, this researcher concluded that venturing into the handling of banana as new, separate business line is the best option for XYZ Corporation to grow competitively and profitably.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, March 2006.
Keywords: Strategic plan